PEWARISAN KESENIAN SALUANG PAUAH DI KECAMATAN PAUAH KOTA PADANG - Eka Putri Wardana; Marzam Marzam; Yensharti Yensharti (SENDRATASIK UNP, 2013)
Abstract Saluang Pauah artistic is one of the traditional arts wich has been living and developing in Pauah regency in Padang. Saluang Pauah is an art that combines vocal (dendang, in Minangkabau language) and it is in the same time followed by Saluang Pauah. This kind of art regenerates in the society through family’s relation ship and environment (informal way).   Kata kunci: pewarisan, Saluang Pauah, informal